Assessment of atmospheric correction methods in MSI imagery for deriving bathymetry and substrates of shallow-water coral reefs - Wei Huang; Wei Huang; Wei Huang; Wei Huang; Jun Zhao; Mingjie Li; Mingjie Li; Mingjie Li; Quansheng Lou; Quansheng Lou; Nanyang Yan; Nanyang Yan; et al. (Frontiers in Marine Science)
Accurate atmospheric correction (AC) is a crucial procedure for monitoring coral reef habitat in shallow waters via remote sensing techniques. In this study, three commonly used AC processors—Dark Spectrum Fitting (DSF), Case 2 Regional Coast Color processor (C2RCC), and Polymer—were applied to evaluate their performance on Sentinel-2 MSI imagery of coral reef areas in the Xisha Islands, South China Sea. Since the latter two processors incorporate a sunglint removal approach, additional procedures were applied to DSF. These include short-wave infrared band Glint Correction (GC), DeGlint (DG), and near-infrared band intercept (DG865) algorithms to enhance glint correction after the DSF processor. The results demonstrate that Polymer outperforms the DSF method (either standalone or with glint corrections) and C2RCC. Polymer-derived remote sensing reflectance showed excellent agreement with in situ measurements, with R2 > 0.95 in 3-hour matches and R2 > 0.65 in 6-hour matches in visible bands (443nm-665nm). It effectively removed most of the glint contamination in the NIR bands (740nm,783nm), while revealing contributions from bottom reflections. Under various image conditions, Polymer consistently delivered the highest bathymetry accuracy (R2: 0.51 - 0.85) and the most stable substrate classifications. This study underscores the critical role of accurate AC in retrieving bathymetry and coral reef substrate information from optically shallow waters using medium- to high-resolution MSI imagery. Polymer proves to be a robust tool for precise remote sensing of coral reefs, offering superior performance even in challenging conditions.